Integrating Indigenous Knowledge and Traditional African Governance into Climate Policy: Legal and Strategic Implications - Ojeh, Vincent Nduka; Nicodemus, John Bongwi (Environmental Ethics & Law, 2025)
This study examines how traditional African governance systems and indigenous knowledge can be more effectively integrated into national and regional climate strategies, with particular attention to legal and policy implications. Using a qualitative narrative review combined with doctrinal legal analysis, the paper synthesizes international legal instruments, regional African climate frameworks, national legislation, and selected judicial decisions. The analysis shows that indigenous governance systems such as communal land management, customary institutions, and traditional ecological knowledge have supported climate adaptation, biodiversity conservation, and sustainable resource management across Africa. However, their contribution remains constrained by weak statutory recognition, fragmented institutional arrangements, and unresolved land tenure conflicts. The study finds that prevailing climate frameworks often acknowledge indigenous knowledge normatively but fail to embed it within enforceable legal and institutional mechanisms. This gap undermines both climate effectiveness and climate justice. The paper concludes that legally anchored integration of traditional governance systems through targeted legal reforms, institutional coordination, and multilevel governance approaches can strengthen climate resilience, enhance community participation, and improve access to international climate finance. The study contributes to climate law and governance scholarship by clarifying pathways for aligning indigenous governance with formal climate policy across Africa.